Are Recessions Good for Educational Attainment? - Carsten Ochsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In this study, we examine how economic performance during the child-specific primary school phase, during which teachers make recommendations regarding secondary school level, affects the educational level achieved ultimately by these children. Using data for Germany, we find that an economic downturn, coupled with increased unemployment, affects children's education attainment negatively. In terms of monetary units, the average effect of the 1993 German recessionon children's educational attainment corresponds to a loss of average monthly household equivalence income of about 50%. A second important conclusion is that children who live in regions that experience poor economic performance over longer periods are, on average, less educated than children who live in more affluent regions. Since human capital is a determinant of economic growth, declining school performance ultimately hampers future growth potential.
Keywords: I21; E24; J10; J22; 330; educational attainment; educational tracking; macroeconomic uncertainty; family structure; intergenerational link; parental labor supply; Kinder; Bildungsniveau; Konjunktur; Strukturschwache Region; Bildungsinvestition; Deutschland